Urban Green Space and Human Health: an Environmental Justice Perspective - Ning, Yueqiao (International Journal of Natural Resources and Environmental Studies, 2024)
Urban green spaces have been shown to provide many of the environmental and social benefits associated with improving the quality of life of residents. However, urban population growth combined with densifying urban planning policies, such development may lead to an unequal distribution of green spaces in cities. As a result, access to green space is increasingly recognized as an environmental justice issue. Based on the Science Citation Index (SCI) core collection database, this paper focuses on the recent research progress of environmental justice research in urban parks and green spaces. This literature documents access to urban parks across socioeconomic and ethnic groups, the extensive benefits of parks for public health and sustainability. The increasing supply of urban green space in many areas of the United States, while emphasizing its diversity and inclusiveness in use, will help alleviate the injustice of urban green space. However, adding too many new urban green spaces and increasing residents' access to parks may lead to green gentrification. In Europe, research is already exploring models of public participation that can promote spatial justice in cities. In China, research on environmental justice in urban green spaces is just emerging and has the potential to be linked to future research on green gentrification, multi-objective use of urban infrastructure, public participation, big data analysis, and community programming.